2015
DOI: 10.1186/s12888-015-0430-0
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of treatment for tics among young people with Tourette syndrome and their parents: a mixed methods study

Abstract: BackgroundTourette syndrome (TS) among young people is associated with psychosocial difficulties and parents play an important role in the management of the condition. Clinical guidelines have been developed for the treatment of TS and tics, but little is known about how young people and their parents perceive their treatment options or their desired outcomes of treatment. The aim of this study is to explore perceptions of treatments for tics among young people with TS and their parents.MethodsIn-depth intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 34 publications
2
63
0
Order By: Relevance
“…Attitudes toward treatment were investigated using a survey of 295 parents of youth with TS and interviews with 42 young people with TS 83 . These subjects were identified through Tourettes Action , a non-profit organization in the U.K.…”
Section: Resultsmentioning
confidence: 99%
“…Attitudes toward treatment were investigated using a survey of 295 parents of youth with TS and interviews with 42 young people with TS 83 . These subjects were identified through Tourettes Action , a non-profit organization in the U.K.…”
Section: Resultsmentioning
confidence: 99%
“…Focus groups with children in medical settings may require more commitment from parents and thus potentially bias the sampling frame. Individual interviews can be carried out in the children's home, or for adolescents, by phone [41] thus widening access.…”
Section: Kieranmentioning
confidence: 99%
“…These survey data align with other evidence that patient demand for CBIT currently exceeds availability. In a mixed methods study of 295 parents of young people with TS and 42 youths with TD, 76% of parents reported that they wanted CBIT to be available for their child, and roughly one-third of parents and half of young people surveyed reported a lack of knowledgeable providers in their geographic region (Cuenca et al, 2015). Moreover, Tourette.org had close to 60,000 searches for CBIT in the last year (TAA, personal communication, 2018).…”
Section: Pre-conference Surveymentioning
confidence: 99%